PENGARUH METODE BERMAIN TERHADAP HASIL BELAJAR LOMPAT JAUH PADA SISWA DI SMK NEGERI 11 CEMPAKA - Riko Tridiansah; Agung Mahendra; Husni Fahritsani (STKIP Subang, 2023)
The purpose of this study was to find out whether the playing method can improve long jump learning outcomes for students at SMK Negeri 11 Cempaka. The method in this study was a quasi-experimental or quasi-experimental research. The variable in this study is the dependent variable, namely the long jump learning outcomes, and the independent variable, namely the playing method. The research design used in this study is in the form of One-Group Pretest – Posttest – Design. The population in this study were all students of class X1, totaling 30 people. The sampling technique used random sampling technique. Based on the type of research this research is descriptive quantitative. The test instrument used is from the learning implementation plan. Data analysis used the t test with a significance level of 5%. The results showed that there was a significant effect of the playing method on the long jump learning outcomes of students at SMK Negeri 11 Cempaka with a t count of 5.291 > t table of 1.701